Dampak Modernisasi Terhadap Pergeseran Nilai Pada Adat Perkawinan Suku Mandailing Di Desa Sirambas Panyabungan Barat - Khodijah Hsb, Siti; Elly Warnisyah Harahap (Universitas Islam Negeri Raden Intan Lampung, 2025)
Modernization often brings changes to the social and cultural structure of a society. In the context of the Mandailing tribe's marriage customs, modernization can cause a shift in values ​​that were previously considered sacred, such as the marriage process which is full of traditional ceremonies, to become simpler or influenced by more practical marriage practices and oriented towards modern trends. This shift can affect the way society views the importance of traditional ceremonies, or even cause a decrease in the interest of the younger generation to preserve these traditions. Marriage customs are not only related to rituals, but also to the cultural identity of the Mandailing tribe. This study aims to determine the effect of modernization on the marriage customs of the Mandailing tribe. The research method used is a qualitative method. The data collection techniques are observation, interviews and documentation. From this study it was found that modernization has brought significant changes to the way customs are carried out, especially in terms of marriage ceremonies. In the Mandailing tribe, marriage customs have a series of rituals that are quite long and involve various parties, such as makkobar which takes a long time. Modernization causes the marriage ceremony to be simplified or eliminate some traditional elements.